2021
DOI: 10.34172/jlms.2021.86
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the 1064 nm Wavelength in Photobiomodulation: A Systematic Review and Meta-Analysis

Abstract: Introduction: Photobiomodulation or low-level laser therapy (LLLT;<0.5 W) has been used as a non-invasive treatment for various medical indications. Short (visible; 635-650 nm) and longer (invisible; 810-850 nm and 915-980 nm) near-infrared wavelengths have been commonly used, but power setting deficiencies or incorrect wavelength settings can cause negative outcomes. The 1064 nm wavelength as the longest wavelength is a relative newcomer in high-powered (>0.5 W) laser photobiomodulation therapy (HPL-PBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…According to Tripodi et al (54), there was a positive, substantial effect for reduction in pain in tendinopathy groups that completed PBM with exercise when compared with groups that completed sham PBM with exercise. Penberthy and Vorwaller (45) found a large effect for reduction in pain and improved functional outcome measures when using PBM at 1,064 nm. A systematic review by Vanin et al (56) found a positive, moderate effect of PBM on exercise performance (i.e.,—strength, power, and endurance) and muscular fatigue in healthy individuals during exercise when compared with a placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…According to Tripodi et al (54), there was a positive, substantial effect for reduction in pain in tendinopathy groups that completed PBM with exercise when compared with groups that completed sham PBM with exercise. Penberthy and Vorwaller (45) found a large effect for reduction in pain and improved functional outcome measures when using PBM at 1,064 nm. A systematic review by Vanin et al (56) found a positive, moderate effect of PBM on exercise performance (i.e.,—strength, power, and endurance) and muscular fatigue in healthy individuals during exercise when compared with a placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Because HILT provides more intense energy to deeper tissues than low-intensity laser therapy, its ability to repair damaged tissues and eliminate painful stimuli is more obvious 8 . A comprehensive meta-analysis reported that spinal disorders can be effectively treated with a high-intensity 1064-nm laser 24 . In a study on patients with chronic neck pain, Alayat et al 25 determined that HILT + EX increased the cervical ROM and significantly reduced VAS and the NDI compared with PL + EX.…”
Section: Discussionmentioning
confidence: 99%
“…8 A comprehensive meta-analysis reported that spinal disorders can be effectively treated with a high-intensity 1064-nm laser. 24 In a study on patients with chronic neck pain, Alayat et al 25 determined that HILT + EX increased the cervical ROM and significantly reduced VAS and the NDI compared with PL + EX. In another study on patients with chronic low back pain, HILT + EX was superior to HILT alone and PL + EX regarding pain and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Several hypotheses have been put forward to explain the primary responses following the absorption of laser light, including singlet oxygen hypothesis, redox property alteration hypothesis, nitric oxide hypothesis, transient local heating hypothesis, transient local heating hypothesis, and superoxide anion hypothesis [40,41]. Moreover, laser irradiation can activate components of the mitochondrial respiratory chain, initiate cell signaling, and promote a cascade of cellular proliferation and protective responses [42]. This leads to changes in the synthesis of DNA, RNA, proteins, and enzymes, or alterations in cell membrane properties, ultimately resulting in enhanced proliferation or differentiation of chondrocytes [43,44].…”
Section: Discussionmentioning
confidence: 99%